2016
DOI: 10.1049/iet-cds.2015.0243
|View full text |Cite
|
Sign up to set email alerts
|

Generalised operational floating current conveyor based instrumentation amplifier

Abstract: This paper proposes two generalised instrumentation amplifier topologies which can operate in voltage, current, transadmittance, and transimpedance mode. Each topology is a two stage structure, wherein an amplifier is used as first stage in the first topology and a converter is employed in the second one. The second stage is difference amplifier for both the structures. The theoretical proposition is verified through operational floating current conveyor (OFCC). The effect of non-idealities of OFCC on system p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 34 publications
(235 reference statements)
0
13
0
Order By: Relevance
“…Figure 10 Various performance parameters such as CMRR, its bandwidth and CMRR gain bandwidth product (GBP), are compared for available references along with proposed topology parameters and are listed in Table 3. As the IAs given in [11], [12], [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] and the proposed one have been tested for different differential gains and at different power supply voltages, it is not fair to compare these on the basis of gain and power consumption.…”
Section: Simulation and Experimental Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 10 Various performance parameters such as CMRR, its bandwidth and CMRR gain bandwidth product (GBP), are compared for available references along with proposed topology parameters and are listed in Table 3. As the IAs given in [11], [12], [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] and the proposed one have been tested for different differential gains and at different power supply voltages, it is not fair to compare these on the basis of gain and power consumption.…”
Section: Simulation and Experimental Resultsmentioning
confidence: 99%
“…e. Both VM and CM active blocks are employed in [29][30][31], [36], [37] therefore the bandwidth is governed by VM block. f. Component matching is needed in [12], [22][23][24], [27][28][29][30][31] for proper operation. [12 Figure 5(a)] and only two resistors without matching constraint.…”
Section: Ijece Issn: 2088-8708 mentioning
confidence: 99%
See 2 more Smart Citations
“…After extensive investigation of references , it is observed that only few IA are existing that uses current-mode ABB having both input and output as current i.e. I-I [24,[27][28][29][30][31][32][33][34] while V-V CMIA are given in literatures [16,17,30,33,[35][36][37][38], V-I CMIA in [16,17,33] and I-V CMIA in [25,33,39]. The different current mode blocks based IA have been designed based on MOS transistors biased in subthreshold region [24], , current operational amplifier (COA) [27,28], CDTA [29], current feedback operational amplifier (CFOA) [30], MOS based configuration [31], current difference buffer amplifier (CDBA) [32], operation floating current conveyor (OFCC) [33], second generation current controlled conveyor (CCCII) [34].…”
Section: Introductionmentioning
confidence: 99%